Power and Violence: The Making of "Modernity," a Conversation with Malcolm Blincow - Yon, Daniel (Anthropologica, 2015)
Political anthropologist Malcolm Blincow, recipient of a York Award for teaching, developed a reputation for taking seriously the anthropology department’s principle of "making knowledge count" (to borrow the title from the edited collection by one of the department’s scholars, Peter Harries Jones). My conversation with Malcolm focused specifically on some of the thinking that informs his popular third-year undergraduate course, Power and Violence: The Making of "Modernity." Without recourse to reductionism, Malcolm’s own personal and professional history as a political anthropologist may have shaped the specific interests and concerns that are reflected in the development of this course.